Interfering with the Sugar Code: Ten Years Later. Issue 30 (15th April 2020) - Bernardi, Anna; Sattin, Sara
Abstract : This paper reviews the past ten years of our research in the field of glycomimetics synthesis and design. The structure‐based design of mono‐ and polyvalent lectin ligands is one of the three main areas that we have explored in this period. We summarize here our work on ligands targeted against the dendritic cell receptor DC‐SIGN. A second direction we have followed involves the discovery of lectin antagonists by screening of glycomimetic libraries. This approach has led to interesting hits against cholera toxin and related bacterial enterotoxins, as well as, in a different campaign, against the human C‐type lectin dectin‐2. Underlying both approaches, the development of robust synthetic methodologies for the rapid and selective synthesis of unnatural glycoconjugates has been our attempt to contribute to the diversification and enrichment of the chemical toolbox of glycoscience. Abstract : With the aim of interfering with the information (sugar code) exchanged between glycans and their protein receptors, we have been developing carbohydrate mimics (glycomimetics) which are more efficient and more selective than naturally occurring saccharides. Here we outline our efforts over the past decade.